A Review Literature of Netra Swasthya Upakrama (International Journal of Ayurveda and Pharma Research, 2023)
Shalakyatantra is one of the important branches of Ayurveda dealing with diseases and treatment of organs situated above the clavicle. As it deals with sense organs it is a highly specialized one. One should always make all sincere efforts to protect the eyes and treat eye diseases as it is one of the important sense organs. Ayurvedic literature gives equal importance to the prevention of disease with a cure. Acharyas have explained various regimens and protocols for a healthy life in Dincharya (daily routine) and Rutucharya (seasonal routine). Some of these regimens can be considered to be designed especially for the well-being of eyes like Anjana, Nasya, etc. These therapeutic procedures are useful if done scientifically and followed the protocol. Sushruta has mentioned 76 eye diseases out of which treatable diseases are treated with systemic as well as local treatment. Kriyakalpa is one of the local treatments. Various therapeutic procedures which are formulated with different drugs and different routes of drug administration according to Dosh, Satmya, and Kal have been explained to avoid the diseased condition. Being a local therapeutic procedure, fast action and penetration of drugs through ocular tissue raises the importance of Kriyakalpa in ocular diseases. Likewise, various regimens explained in Dinacharya and Rutucharya are important to maintain ocular health to avoid ocular diseases.